Transfusion Transmitted Infections (TTIS) Among Blood Donors of Sukkur (Medical Forum Monthly, 2024)
ABSTRACTObjective: To estimate an approximate disease burden of HIV, HBV, HCV, and Syphilis in healthy blood donors.Background: Blood transfusion department not only screen transmitted infections but also give clue about the prevalence of these infections in healthy population. The objective of this study was to estimate an approximate disease burden of HIV, HBV, HCV, and Syphilis in healthy blood donors, so as to determine how well we are doing in fight against these killers. As most of these healthy blood donors are first time donors aged 18-60 years, the results can also be utilized to estimate the prevalence in healthy population of this age group.Study Design: Retrospective Study.Place and Duration of Study: This study was conducted in blood Bank of Ghulam Muhammad Mahar Medical College Hospital Sukkur from January 2008 to December 2010.Materials and Methods: All healthy blood donors reporting to the blood bank in the specified study period were screened for HIV, Hepatitis B, C and Syphilis.Results: A total of 7085 were screened, out of these 364 donors (5.14%) were seropositive for hepatitis C, 268 (3.78%) were seropositive for hepatitis B, 36 (0.5%) were seropositive for Syphilis and only 4 (0.05%) had shown seropositivity for HIV.Conclusion: Transfusion transmitted infections are a major threat associated with unscreened blood donations. In Pakistan the prevalence of hepatitis B and C is very high in occult form. Selection of healthy blood donors and public awareness programs targeting local community will be an important measure to stop its transmission through blood transfusion.